Vultures and others scavenger vertebrates associated with man-sized pig carcasses: a perspective in Forensic Taphonomy - Demo, Caroline (2013)
The activity of vertebrates that feed on corpses can modify the chronology of the decomposition process and interfere with postmortem interval estimates. Further, by destroying the soft parts of the cadaver, scattering, burying or causing the disappearance of bones, it can entirely change the crime scene. In this study, we simulated a clandestine cemetery in an area of Cerrado located inside a farm in Brasília, Distrito Federal. Three domestic pigs of the size of a human of about 60 kg were placed on the ground in different periods of 2010 and 2011. We recorded four species of birds and one of mammal eating the carcasses: 1) Cathartidae: Coragyps atratus (Bechstein, 1973), Cathartes aura (Linnaeus, 1758), Sarcoramphus papa (Linnaeus, 1758); 2) Falconidae: Caracara plancus (Miller, 1777); and 3) Felidae: Leopardus pardalis (Lund, 1840). The behavior of these animals interfered in the decomposition process and resulted in the dispersion and loss of bony parts.